2017
DOI: 10.1186/s12882-017-0571-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural deposits appearing as “zebra bodies” in renal biopsy: Fabry disease?– comparative case reports

Abstract: BackgroundFabry Disease (FD) is a genetic disorder caused by alpha-galactosidase A deficiency. Certain drugs, such as hydroxychloroquine, can produce renal deposits that mimic morphological findings seen in FD, characterizing a type of drug-induced renal phospholipidosis.Case presentationCase 1: A 28-year-old female patient with systemic lupus erythematosus who had been using hydroxychloroquine for 14 months presented subnephrotic proteinuria. Renal biopsy showed deposits compatible with FD. Neither activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 22 publications
2
53
1
4
Order By: Relevance
“…This situation is associated with the progression of interstitial fibrosis [8]. Recent studies have demonstrated that IL-17, a proinflammatory cytokine released from T helper 17 (Th17) cells, concomitantly increases the expression of TGF-b and has a predictive value on graft survival [4,9,10]. TGF-b plays a role in the differentiation of naive lymphocytes to the Th17 subgroup.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This situation is associated with the progression of interstitial fibrosis [8]. Recent studies have demonstrated that IL-17, a proinflammatory cytokine released from T helper 17 (Th17) cells, concomitantly increases the expression of TGF-b and has a predictive value on graft survival [4,9,10]. TGF-b plays a role in the differentiation of naive lymphocytes to the Th17 subgroup.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, higher levels of intrarenal infiltrating Th17 cells in renal allograft tissues have been associated with the progression of fibrosis and tubular atrophy. Tacrolimus-based immunosuppression has been shown to be inadequate to suppress Th17 cells during the early post-transplantation period in kidney transplant recipients [4,9]. There are conflicting data regarding the effects of calcineurin inhibitors on the expression of fibrogenic molecules such as TGF-b [11e13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was proposed a score to standardize the report of the histological alterations in Fabry nephropathy 69 . It is important to bear in mind that some medications, such as amiodarone and chloroquine, can lead to the formation of tissue lipid deposits, mimicking Fabry disease, in different organs, such as the kidneys and cornea 70 .…”
Section: Fabry Diseasementioning
confidence: 99%
“…The main side effect of HCQ is retinal toxicity 1. Another less well-known side effect is a drug-induced phospholipidosis: a phospholipid storage disorder characterised by an accumulation of multilamellar bodies (myeloid bodies) in cells and tissues, associated with clinical toxicities (kidney injury, myopathy) that leads to histological abnormalities as cytoplasmic vacuolisation, and ultrastructural changes with intracellular osmiophilic structures called the ‘zebra bodies’ 2–11. These lesions are also specifically observed in Fabry disease (FD), an X-linked inborn deficiency of the lysosomal enzyme alpha-galactosidase A that causes an accumulation of globotriaosylceramide leading to cellular dysfunction 12.…”
Section: Introductionmentioning
confidence: 99%